Heat Extremes Driven by Amplification of Phase‐Locked Circumglobal Waves Forced by Topography in an Idealized Atmospheric Model - Jiménez‐Esteve, B.; Kornhuber, K.; Domeisen, D. I. V. (Geophysical research letters, 2022)
Heatwaves are persistent temperature extremes associated with devastating impacts on human societies and ecosystems. In the midlatitudes, amplified quasi‐stationary Rossby waves have been identified as a key mechanism for heatwave occurrence. Amplified waves with preferred longitudinal locations lead to concurrent extremes in specific locations. It is therefore important to identify the essential components in the climate system that contribute to phase‐locking of wave patterns. Here, we investigate the role of dry atmospheric dynamics and topography in causing concurrent heatwaves by using an idealized general circulation model. Topography is included in the model experiments as a Gaussian mountain. Our results show that amplified Rossby waves exhibit clear phase‐locking behavior and a decrease in the zonal phase speed when a large‐scale localized topographic forcing is imposed, leading to concurrent heat extremes at preferred locations. Plain Language Summary Heatwaves are among the most deadly natural disasters. Since climate projections indicate an increase in the severity and frequency of heatwaves, it is important to understand which processes are responsible for their occurrence. Heatwaves in midlatitudes tend to be associated with atmospheric waves, characterized by a strong meandering of the jet stream. Occasionally, waves tend to reduce their longitudinal propagation speed along with an amplification of their amplitude in preferred locations. This behavior is known as phase‐locking and can lead to extreme weather events, occurring simultaneously in different regions, as for example, during the Russian heatwave and Pakistan flooding in 2010. Here, we investigate the role of large‐scale mountains in driving concurrent heat extremes. We use simulations from an idealized atmospheric model with an idealized mountain, and keeping only the essential atmosphere dynamics represented. In the model, topography alone leads to the occurrence of phase‐locked circumglobal waves and localized heatwaves. The eastward velocity of the waves is substantially reduced due to topography, which can be linked to an increase in heatwaves in specific areas. This research lays the basis for understanding the fundamental factors that lead to concurrent extreme weather events, which is important to improve their forecasts. Key Points The inclusion of topography in an idealized model setup yields global‐scale slow‐moving Rossby waves with preferred longitudinal locations When these slow‐moving Rossby waves amplify they lead to an increased frequency of concurrent heatwaves in preferred longitudinal locations In the model, zonal wavenumbers 5 and 6 exhibit the strongest anomalies, which strongly impact temperature and heatwave frequency